Hubungan Tingkat Pengetahuan dan Sikap Tentang Teledentistry dengan Perilaku Penggunaan Teledentistry pada Pasien RSGM YARSI - Rendy Faisal; Dharma Satya Aprianti; Helwiyah Umniyati; Siti Nur Riani (Lembaga Penelitian Universitas YARSI, 2024)
Introduction: Teledentistry is a service that combines the field of dentistry with technologyand telecommunications. The use of teledentistry has increased during the COVID-19pandemic. Teledentistry can improve the quality of dental care and also enable remote care forpatients. Research objective: This study aims to determine whether there is a relationshipbetween knowledge and attitudes towards teledentistry and the behavior of using teledentistryin patients at RSGM YARSI. Method used in research: The research was conducted on 90patients at RSGM YARSI through questionnaire completion. The data obtained were thenanalyzed using the chi-square test. Results: The chi-square test for knowledge aboutteledentistry showed a significance value of 0.691 (p < 0.05). The chi-square test for attitudestowards teledentistry showed a significance value of 0.078 (p < 0.05). Conclusion: There is nosignificant difference in the level of knowledge of RSGM YARSI patients regarding thebehavior of using teledentistry. There is no significant difference in the attitudes of RSGMYARSI patients towards the behavior of using teledentistry.